Conventional treatment of a metaldehyde-intoxicated cat with additional use of low-dose intravenous lipid emulsion. Issue 2 (August 2020) - Bergamini, Ilaria; Mattavelli, Clara; Grossi, Giorgio; Magagnoli, Ilaria; Giunti, Massimo
Case summary: An adult male intact domestic shorthair cat was presented for acute onset of generalised tremors, stupor, horizontal nystagmus, anisocoria and bilateral absence of pupillary light and palpebral reflexes. Response to intravenous (IV) administration of benzodiazepines was minimal; thus, the induction of general anaesthesia with propofol, midazolam and dexmedetomidine was necessary to control clinical signs. Following a clinical suspicion of neurotoxicosis, a low-dose constant rate infusion (CRI) of IV lipid emulsion (ILE) was started. Phenobarbital and a low-dose CRI of ketamine were also used for neuroprotective purposes. Metaldehyde intoxication was confirmed by qualitative faecal toxicological analysis after discharge. Anaesthetic drugs were progressively tapered and stopped after 28 h and extubation was possible after 44 h. The cat was discharged 8 days after admission with a complete recovery of the clinical signs. Relevance and novel information: To the authors' knowledge, this is the first report to describe a case of metaldehyde toxicosis in a cat treated with intensive supportive care and an additional low-dose CRI of ILE.